Target costing practices: a review of literature / Hussein H. Hamood, Normah Omar and Suzana Sulaiman - Hamood, Hussein H.; Omar, Normah; Sulaiman, Suzana (Universiti Teknologi MARA Cawangan Selangor, 2011)
Advanced management accounting techniques have been seen by IFAC’s (1998) evolution framework as a shift towards value creation and providing timely and relevant information needed for decision making. The adoption of advanced management accounting techniques, such as Target Costing (TC), requires organizations to be able to deal with challenges and problems that may occur during the adoption process. In today’s competitive environment, many companies are continuously seeking to produce high quality and functional products based on customers’ expectations gleaned from market research. In meeting these objectives, TC has been widely adopted under the original leadership of Japanese TC since the 1960s. Hence, this paper aims to review the literature investigating the TC practices in non-Japanese contexts. The study focuses on the TC concept and its application in ten countries. The information is based on 35 articles which were written in English, translated, and published in various refereed international journals. Furthermore, this paper discusses the factors, issues and challenges that influence TC application in the countries, as well as the applicability level of this technique in the Malaysian context. In general, the evidence reviewed reveals a significant variation in TC practices, steps followed and participants involved in TC application in the 10 countries surveyed. In addition, environmental factors and issues relating to product features improvement are crucial for a successful implementation of TC. The paper concludes by stating that efficient supply chain management is an important element in successful TC implementation. Essentially, manufacturing firms should establish closer ties with suppliers who have a distinctive role to enhance product value in TC practices.